The Mashahir Al-Ulama Al-Amsar Of Ibn Hibban Al-Busti (d. 354ah/965CE) - Muhammad Yusoff, M. F. (Universiti Sains Islam Malaysia, 2024)
Journal of Hadith Studies Vol. 2 No. 2(December 2017) e-ISSN: 2550-1448